Minimising tibial fracture after unicompartmental knee replacement: a probabilistic finite element study - Pegg, EC; Walter, J; D'Lima, DD; Fregly, BJ; Gill, HS; Murray, DW (Elsevier, 2019)
Background Periprosthetic tibial fracture after unicompartmental knee replacement is a challenging post-operative complication. Patients have an increased risk of mortality after fracture, the majority undergo further surgery, and the revision operations are less successful. Inappropriate surgical technique increases the risk of fracture, but it is unclear which technical aspects of the surgery are most problematic and no research has been performed on how surgical factors interact.